The Urgency of Policy Legitimacy in the E-voting System in Bantaeng Village Elections - Halwan, Muhammad (Indonesian Journal Of Law Studies, 2024)
Digitization has touched various aspects of community life in Indonesia, including the implementation of e-voting in several regions' village head elections (Pilkades). This study aims to determine the urgency of policy legitimacy in e-voting in Bantaeng Regency. The implementation of the e-voting system is seen as a response to the efforts of digital democracy transformation and a manifestation of political innovation. This study is based on qualitative research, gathering data through observation, interviews, and questionnaires. Qualitative data analysis begins with data display or presentation, data triangulation, and interpretation of data and findings. The results of this study indicate that the stages from formulation to implementation in the e-voting system must be followed based on policy legitimacy. Hence, policy formulation is born, which is enshrined through the Regent's Regulation. The legitimacy process of e-voting through the Regent's Regulation provides authority or authorization for a formulated policy to be made official and enforceable. Regulations born through the Regent's Regulation provide valid legitimacy for the implementation of the e-voting system in e-voting Pilkades in Bantaeng Regency.